BUDIDAYA JAMUR PERUSAK KAYU IV. KULTUR JAMUR PADA SUBSTRAT SERBUK GERGAJI YANG DIPERKAYA - Sihati Suprapti; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
Oyster  mushroom (Pleuroius ostreatus) has been cultivated on five sawdust  media  of  five wood  species, i.e. durian (Durio  zibethinus Murr.),  jeungjing  (Albizia  falcataria  (L.)  Fosb.).  manii (Maesopsis eminii Engl.),  rubber  (Hevea brasiliensis Muell.  Arg.)  and  coconut   (Cocos  nucifera  L.). The  composition  of  the  media  was 100  % saw dust, 80 % sawdust + 20 % rice  bran,  99.5 % sawdust  +  0.5 % lime,  99 % sawdust + 0.5 % lime + 0.5 % trisuperphosphate    (TSP),  and 97.5 % sawdust + 0.5 % lime  +  0.5 %  TSP + 1.5 % gypsum.  Each  media was mixed  with sufficient distilled water. The  media  was allowed to cool after  autoclave  sterilization   before  being  inoculated   with  pure  culture  of  the  mushroom.   The  mature  mushroom was harvested  daily  after  the growth  of  fruiting  body.